Hidden photon and axion dark matter from symmetry breaking - Kazunori Nakayama; Wen Yin (Journal of High Energy Physics, 2021)
Abstract A light hidden photon or axion-like particle is a good dark matter candidate and they are often associated with the spontaneous breaking of dark global or gauged U(1) symmetry. We consider the dark Higgs dynamics around the phase transition in detail taking account of the portal coupling between the dark Higgs and the Standard Model Higgs as well as various thermal effects. We show that the (would-be) Nambu-Goldstone bosons are efficiently produced via a parametric resonance with the resonance parameter q ∼ 1 at the hidden symmetry breaking. In the simplest setup, which predicts a second order phase transition, this can explain the dark matter abundance for the axion or hidden photon as light as sub eV. Even lighter mass, as predicted by the QCD axion model, can be consistent with dark matter abundance in the case of first order phase transition, in which case the gravitational wave signals may be detectable by future experiments such as LISA and DECIGO.